Switch the powers

Level 2

Find the number of ordered pairs of integers ( x , y ) (x,y) such that x y x\neq y and x 2 + y 3 = x 3 + y 2 x^2+y^3=x^3+y^2


The answer is 2.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Rewrite the equation as x 2 y 2 = x 3 y 3 x^{2} - y^{2} = x^{3} - y^{3}

Factor it to obtain ( x y ) ( x + y ) = ( x y ) ( x 2 + x y + y 2 ) (x - y)*(x + y) = (x - y)*(x^{2} + xy + y^{2})

Given x y x - y cannot be 0 0 , we have: x + y = x 2 + x y + y 2 x + y = x^{2} + xy + y^{2}

Rearranging all terms in one side, x 2 + x ( y 1 ) + ( y 2 y ) = 0 x^{2} + x*(y - 1) + (y^{2} - y) = 0

Solve for x x .

x = ( ( 1 y ) + s q r t ( y 2 2 y + 1 4 y 2 + 4 y ) ) / 2 x = ((1 - y) +- sqrt(y^{2} - 2y + 1 - 4y^{2} + 4y))/2

x = ( ( 1 y ) + s q r t ( y 2 + 2 y + 1 4 y 2 ) ) / 2 x = ((1 - y) +- sqrt(y^{2} + 2y + 1 - 4y^{2}))/2

x = ( ( 1 y ) + s q r t ( ( y + 1 ) 2 ( 2 y ) 2 ) ) / 2 x = ((1 - y) +- sqrt((y + 1)^{2} - (2y)^{2}))/2

x = ( ( 1 y ) + s q r t ( ( 1 + y ) ( 1 y ) ) / 2 x = ((1 - y) +- sqrt((1 + y)(1 - y))/2

If x x is an integer, then the product ( 1 + y ) ( 1 y ) (1 + y)*(1 - y) must be greater than or equal 0 0 , otherwise we will get a complex number.

Thus, from the inequality we can write: 1 < = y < = 1 - 1 <= y <= 1 . This implies that y y is either 1 , 0 -1, 0 or 1 1 .

Case I: y = 1 y = - 1 .

x 1 = x 2 x + 1 x - 1 = x^{2} - x + 1

x 2 2 x + 2 = 0 x^{2} - 2x + 2 = 0

x = ( 2 + 2 i ) / 2 = ( 1 + i ) x = (2 +- 2i)/2 = (1 +- i) , not valid solutions.

Case II: y = 0 y = 0

x = x 2 , x = 0 x = x^{2}, x = 0 or x = 1 x = 1 . Since y y is different from x x , only the solution ( 1 , 0 ) (1, 0) is valid.

Case III: y = 1 y = 1

x + 1 = x 2 + x + 1 x + 1 = x^{2} + x + 1

x 2 = 0 x^{2} = 0 , so x = 0 x = 0 and we have our second solution, ( 0 , 1 ) (0, 1) .

I noticed a mistake I made on the factorization. Should have been ( 1 + 3 y ) ( 1 y ) (1 + 3y)*(1 - y) , which would have only yielded the cases 0 and 1. Still, the reasoning behind it is correct and led to the right answer.

Alexandre Miquilino - 7 years, 4 months ago
Ben Frankel
Jan 11, 2014

We will at first ignore the requirement that x x and y y must be integers, and manipulate this equation algebraically.

x 2 + y 3 = x 3 + y 2 x 2 y 2 = x 3 y 3 x^2 + y^3 = x^3 + y^2 \:\Rightarrow\: x^2 - y^2 = x^3 - y^3 ( x y ) ( x + y ) = ( x y ) ( x 2 + x y + y 2 ) \Rightarrow\: (x - y)(x + y) = (x - y)(x^2 + xy + y^2)

Because we are given that x y x \neq y , we know that x y 0 x - y \neq 0 , and so we can divide both sides of the equation by ( x y ) (x - y) , and then we can solve for x x in terms of y y .

x + y = x 2 + x y + y 2 ( 1 ) x 2 + ( y 1 ) x + ( y 2 y ) = 0 x + y = x^2 + xy + y^2 \:\Rightarrow\: (1)x^2 + (y - 1)x + (y^2 - y) = 0

By the quadratic formula,

x = 1 y ± 3 y 2 + 2 y + 1 2 x = \frac{1 - y \pm \sqrt{-3y^2 + 2y + 1}}{2}

Because of the negative leading coefficient, we know that f ( y ) = 3 y 2 + 2 y + 1 f(y) = -3y^2 + 2y + 1 is a parabola opening downwards, and so by finding the vertex of this parabola, we can find all possible nonnegative integer values of f ( y ) f(y) . We find the vertex to be at y = 2 6 = 1 3 y = -\frac{2}{-6} = \frac{1}{3} , and so now we only have to check cases for the nonnegative integers less than f ( 1 3 ) = 1 1 3 f(\frac{1}{3}) = 1\frac{1}{3} , which are 1 and 0.

3 y 2 + 2 y + 1 = 1 y ( 3 y + 2 ) = 0 ( x , y ) = ( 1 , 0 ) , -3y^2 + 2y + 1 = 1 \:\Rightarrow\: y(-3y + 2) = 0 \:\Rightarrow\: (x, y) = (1, 0),

3 y 2 + 2 y + 1 = 0 ( 3 y + 1 ) ( 1 y ) = 0 ( x , y ) = ( 0 , 1 ) -3y^2 + 2y + 1 = 0 \:\Rightarrow\: (3y + 1)(1 - y) = 0 \:\Rightarrow\: (x, y) = (0, 1)

So there are 2 \boxed{2} solutions.

Josh Rowley
Jan 10, 2014

First of all, since the equation is symmetrical, if we have some solution ( a , b ) (a,b) then ( b , a ) (b,a) is also a solution. So if the number of solutions where x < y x<y is n n , then the total number of solutions is 2 n 2n . So therefore let us consider when x < y x<y ie. y = x + d y=x+d , where d N d \in \mathbb{N} . Then we can turn the equation into x 2 + ( x + d ) 3 = x 3 + ( x + d ) 2 x^2 + (x+d)^3 = x^3 + (x+d)^2 . Expanding and cancelling leaves us with: 3 x 2 + ( 3 d 2 ) x + ( d 2 d ) = 0 3x^2 + (3d-2)x + (d^2-d) = 0 . Applying the quadratic formula we obtain: x = 2 3 d ± 9 d 2 12 d + 4 12 d 2 + 12 d 6 x = \dfrac{2-3d \pm \sqrt{9d^2-12d+4-12d^2+12d}}{6} x = 2 3 d ± 4 3 d 2 6 x = \dfrac{2-3d \pm \sqrt{4-3d^2}}{6} . Since x R x \in \mathbb{R} then 4 3 d 2 0 4-3d^2 \ge 0 so the only possible value is d = 1 d=1 . Now we can sub this back in: x 2 + ( x + 1 ) 3 = x 3 + ( x + 1 ) 2 x^2+(x+1)^3 = x^3 + (x+1)^2 , and again expanding and cancelling we get 3 x 2 + x = 0 3x^2 + x = 0 so x ( 3 x + 1 ) = 0 x(3x+1) = 0 , so the only integral value for x is 0 0 , yielding y = 1 y = 1 . As we stated at the start this is only half the solutions, so the final answer is 2 \fbox {2}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...